Political (In)tolerance of the Far-Right: The Importance of Agency - Bjånesøy, Lise (Frontiers in Political Science, 2021)
This paper examines the impact of far-right agency on public political tolerance—what the parties on the far right do to disconnect themselves from accusations of extremism and thus increase their political tolerance by the public. Examining such patterns is challenging because of the multiple varieties of party attributes and strategies that are used by the far right. This paper uses a conjoint survey experiment conducted in the Norwegian Citizen Panel. Each respondent was presented with one vignette describing important attributes of a hypothetical far-right initiative and was then asked to evaluate whether this initiative should be allowed to hold an event. The conjoint design makes it possible to test the impact of the ideological and organizational varieties of the far right. The results demonstrate that what the parties on the far right do is crucial for public political tolerance. Denying extremism and excluding extreme members increase tolerance. However, the features that the far right is not in control of, such as its ideological legacy and the fact that some of its members have been convicted of racist speech negatively affect public political tolerance. The paper concludes that the agency of the far right is a necessary but not sufficient condition for public political tolerance of the far right.